Spontaniczność i automatyzm w wypowiedziach modlitewnych Marii Pawlikowskiej-Jasnorzewskiej = Spontaneity and automatism in prayer utterances of Maria Pawlikowska-Jasnorzewska - Wojciechowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper an attempt is made to present language behaviour connected with praying actions excerpted from war notes written by Maria Pawlikowska-Jasnorzewska. The aim of the paper is to examine the structure and stylistic devices of prayer utterances with reference to prayer as a genre. As a result, two aspects will be discussed, that is, spontaneity versus automatism.
Keywords: zapiski; modlitwa prywatna; Pawlikowska-Jasnorzewska, Maria (1891-1945); notes; private prayer